Modeling of low-temperature plasma inhibition and mechanism of Aspergillus flavus on corn kernels surface - Shuai Li; Haiyang Zou; Mo Niu; Yingnan Zeng; Jingxin Song (CyTA - Journal of Food)
This study was conducted to optimize a process of low-temperature plasma treatment for the decontamination of Aspergillus flavus (A. flavus) on corn kernels. Impacts of plasma-treated time (30, 60, 90 s), plasma-treated power (300, 400, 500 W), and vacuum degree (85, 90, 95 Pa) on the decontamination effect in this process were explored. The optimal conditions included vacuum degree at 90 Pa, plasma treating time of 90 s, and plasma treating power of 500 W, under which the A. flavus spores was 4.03 log (cfu/g). Plasma treatment triggered antioxidative defense system, broke cell structures, and dispersed cell contents. A large number of free radicals act on lipids and proteins, and malondialdehyde (MDA) accumulate in large quantities, further leading to damage to cell structures.